6x+1-5c=15

Simple and best practice solution for 6x+1-5c=15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+1-5c=15 equation:


Simplifying
6x + 1 + -5c = 15

Reorder the terms:
1 + -5c + 6x = 15

Solving
1 + -5c + 6x = 15

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -5c + -1 + 6x = 15 + -1

Reorder the terms:
1 + -1 + -5c + 6x = 15 + -1

Combine like terms: 1 + -1 = 0
0 + -5c + 6x = 15 + -1
-5c + 6x = 15 + -1

Combine like terms: 15 + -1 = 14
-5c + 6x = 14

Add '-6x' to each side of the equation.
-5c + 6x + -6x = 14 + -6x

Combine like terms: 6x + -6x = 0
-5c + 0 = 14 + -6x
-5c = 14 + -6x

Divide each side by '-5'.
c = -2.8 + 1.2x

Simplifying
c = -2.8 + 1.2x

See similar equations:

| 5x+8+2x-17=180 | | -6g+1=-41 | | 2.5d+9.75=1+4.25d | | -3b-(6b+12)=-9b+13 | | -40=9g-4 | | 4x+3(x-5)=4(2x+3) | | 3x+3+x-7=180 | | .5x-7=x-5 | | 4n+8=13 | | 3.5d+8.75=5+4.25d | | -12=2x+6 | | 6h-4=32 | | 5c+8-4d-2-c= | | -3(x+1)+5=2(x-6) | | 2.5d+9.25=1+3.25d | | 8x+1=x+8 | | -16+x=-3x+8 | | 2(4x-1)-5=x-7 | | y-3=2x+2 | | 5+5x=23 | | 5+5+x=23 | | h+14.6=-14.6 | | 4q-q+3q-2q= | | s-5.9=19.2 | | 3(2x+5)=14x+7 | | 6.5=-3+j | | 5(x+1)=6x-11 | | 6a-8=7+a | | -3(2-x)=-15 | | F(x)=x^4-8x^3+18x^2+6 | | 3x-7x+5=3-5x | | 18x-28=x+380 |

Equations solver categories